Implementasi Metode Ceramah Tipe Impromtu dalam Peningkatan Belajar Siswa pada Pelajaran Pendidikan Agama Islam di SMP Negeri 3 Air Batu Satu Atap - Ramadani, Ika; Zailani, Zailani (EduInovasi: Journal of Basic Educational Studies, 2024)
SMP Negeri 3 Air Batu Satu Roof in the Islamic Religious Education subject where in this subject teachers still often use the lecture method where students only listen to the teacher during learning, however the teacher also combines the lecture method with other learning methods such as discussion and question and answer methods. This research is at SMP Negeri 3 Air Batu Satu Atap in the Islamic Religious Education subject where in this subject teachers still often use the lecture method where students only listen to the teacher during learning, however teachers also combine the lecture method with other learning methods such as discussion and questioning methods. answer. This research resulted that the lecture method using the impromptu method was able to enliven the class atmosphere and was able to increase interest in learning and also improve student learning outcomes for students at SMP Negeri 3 Air Batu Satu Atap.